Cultural Crossroads in the Middle East The Historical, Cultural and Political Legacy of Intercultural Dialogue and Conflict from the Ancient Near East to the Present Day - Sazonov, Vladimir; Mölder, Holger; Espak, Peeter (Studia Orientalia Tartuensia. Series Nova, 2019)
The region of the Middle East has been called the cradle of mankind. This volume studies historical, cultural, religious, social and political legacies, which play a central role in obstructing intercultural dialogue in the Middle East. The region became home to numerous cultures, religions and ethnicities with long experience of living together in a multicultural environment and has an immense impact on the entire human civilization as first human civilizations were born there. Today, more than 50% of world population follow Abrahamic religions (e.g. Christianity, Islam, Judaism), which have their roots in the Middle East. This book focuses on multiple topics related to the Middle East, including ancient history, the religion and mythology of the Ancient Near Eastern regions, Arabic, Persian and Islamic studies, Persian, Turkish and Arab literature, as well as modern Middle Eastern issues related to politics, security, society and the economy. The volume includes papers by Amar Annus, Tanja Dibou, Peeter Espak, Yoel Guzansky, Ingrida Kleinhofa, Jaan Lahe, Lidia Leontjeva, Aynura Mahmudova, Yossi Mann, Kobi Michael, Holger Mölder, Limor Nobel-Konig, Üllar Peterson, Itamar Rickover, Vladimir Sazonov and Krzyztof Ulanowski.